Alexithymia and Somatization in Chronic Pain Patients: A Sequential Mediation Model - Lanzara, Roberta; Conti, Chiara; Camelio, Martina; Cannizzaro, Paolo; Lalli, Vittorio; Bellomo, Rosa Grazia; Saggini, Raoul; Porcelli, Piero (Frontiers in Psychology, 2020)
Objective To investigate whether chronic pain (CP) patients with somatization reported higher alexithymic traits than those without somatization and to study the different relationships between psychological characteristics, pain, health-related quality of life (HRQL), and somatization. Method A consecutive sample of 134 CP treatment-seeking outpatients were evaluated for alexithymia (TAS-20), somatization (PHQ-15), distress (HADS), HRQL (SF-12), and pain (BPI). Results Patients with somatization (37.04%) reported significantly higher TAS-20 total scores (p < 0.001) and difficulty in identifying feelings (DIF) (p < 0.001) than those without somatization. The somatizer group had also a significantly higher disease duration, severity and interference of pain, distress, and lower HRQL than the non-somatizer group. Hierarchical regression analysis showed that although distress, pain interference and the mental HRQL component are closely related to somatization (R2 = 0.55), DIF was the strongest predictor of severity of somatization (β = 0.31). A sequential indirect effect from DIF to somatization via distress symptoms and pain interference turned out to be significant [95% CI (0.01, 0.09)]. Support was also found for sequential mediation paths from DIF to somatization via distress and mental HRQL [95% CI (0.01, 0.11)]. Conclusions Our results pointed-out that alexithymia, particularly DIF, may be major factor for somatization risk in CP patients. Longitudinal observations are needed for evaluating the role of alexithymia in clinical outcomes.